The Impact of The Covid-19 Pandemic on Vietnam’s Stock Market Volatility - Nguyen Phan Thu , Hang; Le Dinh , Nghi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The paper aims to analyze the impact of the COVID-19 pandemic on Vietnam’s stock market volatility. Using VN-Index data on a daily basis from Jan 01, 2016, to Dec 31, 2021, and employing the GARCH model, the results indicate a significant increase in stock market volatility during the COVID-19 period, except for the third wave of the pandemic in Vietnam. Moreover, the paper also shows that volatility is most significant in the first wave of the pandemic. Therefore, investors should have suitable diversification strategies to manage portfolio risks when investing in the stock market. Moreover, market regulators need to take appropriate policies to manage market risks as the COVID-19 pandemic remains complicated.
Keywords: COVID-19 pandemic; Volatility; Stock market; Vietnam